Cellulose-based resin composition and molded article using the same
By adding an appropriate amount of triphenyl phosphate and metal hydroxyl to the cell carbohydrate resin composition and controlling the content of each component, the problems of insufficient fire protection and mechanical strength of the molded body of the cell carbohydrate resin composition in the prior art are solved, and the significant performance improvement of the composition is achieved.
Patent Information
- Application Number
- JP2023538634
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-29
- Filing Date
- 2022-07-29
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2042-07-29
AI Technical Summary
In the prior art, the cell carbohydrate resin composition has shortcomings in forming molded bodies with excellent fire protection and mechanical strength.
A cell carbohydrate resin composition is used, which includes cell carbohydrate, triphenyl phosphate, anti-drops and metal hydroxylates, and the content of triphenyl phosphate is controlled between 20% and 30% and metal hydroxylates is controlled between 10% and 20%.
The cell carbohydrate resin composition has achieved significant improvement in fire protection and mechanical strength, and can form a molded body with excellent performance.
Smart Images

Figure 0007670387000001 
Figure 0007670387000002 
Figure 0007670387000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cellulose-based resin composition and a molded article using the same. [Background technology]
[0002] Bioplastics made from plant components can contribute to combating oil depletion and global warming, and so they are beginning to be used in durable products such as electronic devices and automobiles, in addition to general products such as packaging, containers, and textiles.
[0003] Conventional bioplastics, such as polylactic acid, polyhydroxyalkanoates, and modified starch, are all made from starch-based materials, i.e., edible parts of plants. Therefore, due to concerns about future food shortages, there is a demand for the development of new bioplastics made from inedible parts of plants.
[0004] A typical example of the raw material for the inedible parts is cellulose, a major component of wood and plants, and various bioplastics using this have been developed and commercialized.
[0005] These plant-derived resins are generally flammable, so flame retardant measures are necessary when they are used in applications that require a high level of flame retardancy, such as housings for home appliances and office automation equipment. In particular, when using resin compositions made from plant-derived resins for the housings of electrical appliances, they need to satisfy flame retardant standards, including the UL94 standard.
[0006] In order to improve flame retardancy, a resin composition containing a flame retardant has been studied. For example, Patent Document 1 discloses a resin composition containing a polylactic acid resin, a cellulose ester, an aromatic polycarbonate resin, a compatibilizer, and a flame retardant. Patent Document 2 discloses a resin composition containing a cellulose ester and a cyclic phosphorus compound having a specific structure. Patent Document 3 discloses a flame-retardant thermoplastic resin composition containing a polylactic acid resin, a flame retardant containing a metal hydrate, and a high-strength fiber. Patent Document 4 discloses a cellulose ester resin composition containing a cellulose ester resin and a phosphoric acid ester having a specific structure. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2006-111858 A [Patent Document 2] JP 2011-241236 A [Patent Document 3] JP 2011-168798 A [Patent Document 4] WO2014 / 002720 issue Summary of the Invention [Problem to be solved by the invention]
[0008] However, Patent Documents 1 to 4 do not fully investigate cellulose resin compositions capable of forming molded articles having excellent flame retardancy and mechanical strength.
[0009] An object of the present embodiment is to provide a cellulose-based resin composition capable of forming a molded article having excellent flame retardancy and mechanical strength, and a molded article formed using the same. [Means for solving the problem]
[0010] One aspect of the present embodiment relates to the following.
[0011] Component (A): Cellulose acetate, Component (B): triphenyl phosphate, triethyl phosphate, tributyl phosphate, tricresyl phosphate, cresyl di-2,6-xylenyl phosphate, and a compound represented by the following formula (I):
[0012] [ka] and one or more phosphate esters selected from the group consisting of compounds represented by Component (C): Anti-drip agent, Component (D): a metal hydroxide, Including, The content of component (B) is 20% by mass or more and less than 30% by mass relative to 100% by mass of the total content of components (A) and (B), A cellulose-based resin composition, in which the content of component (D) is 10% by mass or more and 20% by mass or less relative to 100% by mass of the total content of components (A) to (D). Effect of the Invention
[0013] According to the present embodiment, it is possible to provide a cellulose-based resin composition capable of forming a molded article having excellent flame retardancy and mechanical strength, and a molded article molded using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The cellulose-based resin composition of the present embodiment (also simply referred to as a "resin composition" or a "cellulose acetate resin composition") is Component (A): Cellulose acetate, Component (B): triphenyl phosphate, triethyl phosphate, tributyl phosphate, tricresyl phosphate, cresyl di-2,6-xylenyl phosphate, and a compound represented by the following formula (I):
[0015] [ka] and one or more phosphate esters selected from the group consisting of compounds represented by Component (C): Anti-drip agent, Component (D): a metal hydroxide, Including, The content of component (B) is 20% by mass or more and less than 30% by mass relative to 100% by mass of the total content of components (A) and (B), The content of component (D) is 10% by mass or more and 20% by mass or less, relative to 100% by mass of the total content of components (A) to (D).
[0016] The resin composition of the present embodiment is excellent in flame retardancy and mechanical strength. The present inventors have found that a resin composition contains cellulose acetate, a specific phosphate ester, an anti-drip agent, and a metal hydroxide, and the contents of the phosphate ester and the metal hydroxide are within the respective specific ranges, thereby obtaining a cellulose-based resin composition having both excellent flame retardancy and mechanical properties. Each component will be described below.
[0017] <Component (A)> The cellulose-based resin composition of the present embodiment contains cellulose acetate (also referred to as "CA") as component (A). As the cellulose acetate, one in which acetyl groups have been introduced into at least a portion of the hydroxyl groups of cellulose as a raw material can be used.
[0018] Cellulose is a linear polymer formed by polymerization of β-D-glucose molecules (β-D-glucopyranose) represented by the following formula (1) via β(1→4) glycosidic bonds. Each glucose unit constituting cellulose has three hydroxyl groups (n in the formula is a natural number). In this embodiment, acetyl groups are introduced into such cellulose by utilizing these hydroxyl groups.
[0019] [ka]
[0020] Cellulose is the main component of plants and can be obtained by separating and treating other components such as lignin from plants. In addition to those obtained in this way, cotton (e.g., cotton linters) and pulp (e.g., wood pulp) with a high cellulose content can be used as is or after purification. The shape, size and form of cellulose or its derivatives used as raw materials are preferably in the form of powder with an appropriate particle size and shape in terms of reactivity, solid-liquid separation and ease of handling. Although not limited, for example, fibrous or powdery materials with a diameter of 1 to 100 μm (preferably 10 to 50 μm) and a length of 10 μm to 100 mm (preferably 100 μm to 10 mm) can be used.
[0021] The degree of polymerization of cellulose, expressed as the glucose polymerization degree (average polymerization degree), is preferably in the range of 50 to 5000, more preferably 100 to 3000, and even more preferably 100 to 1000. If the degree of polymerization is too low, the strength, heat resistance, etc. of the produced resin may be insufficient. Conversely, if the degree of polymerization is too high, the melt viscosity of the produced resin may become too high, causing problems in molding.
[0022] The cellulose acetate in this embodiment can be obtained by utilizing the hydroxyl groups of cellulose and introducing acetyl groups.
[0023] The acetyl group can be introduced by reacting a hydroxy group in cellulose with an acylating agent. The acetyl group corresponds to an organic group portion introduced in place of a hydrogen atom of a hydroxy group in cellulose. The acylating agent is a compound having at least one functional group capable of reacting with a hydroxy group in cellulose, and examples of the acylating agent include compounds having a carboxyl group, a carboxylic acid halide group, and a carboxylic acid anhydride group. Specific examples include aliphatic monocarboxylic acids (acetic acid), their acid halides, and their acid anhydrides (acetic anhydride).
[0024] The average number of acetyl groups introduced per glucose unit of cellulose (DS AC) (acetyl group introduction ratio), i.e., the average number of hydroxyl groups substituted with acetyl groups per glucose unit (hydroxyl group substitution degree), can be set in the range of 0.1 to 3.0. In order to fully obtain the effect of introducing acetyl groups, particularly from the viewpoints of water resistance, fluidity, etc., DS AC is preferably 2.0 or more, more preferably 2.2 or more, and even more preferably 2.4 or more. From the viewpoint of obtaining the effect of introducing an acetyl group while fully obtaining the effect of other groups (hydroxyl group, etc.), DS AC is preferably 2.9 or less, more preferably 2.8 or less.
[0025] By introducing the above-mentioned acetyl group into cellulose, the intermolecular force (intermolecular bond) of cellulose can be reduced, and the plasticity of the cellulose acetate resin composition can be improved.
[0026] The more the residual amount of hydroxyl groups, the greater the maximum strength and heat resistance of the cellulose acetate resin composition, but the greater the water absorption. On the other hand, the higher the conversion rate (degree of substitution) of the hydroxyl groups, the lower the water absorption and the greater the plasticity and breaking strain, but the lower the maximum strength and heat resistance. Taking these trends into consideration, the conversion rate of the hydroxyl groups can be appropriately set.
[0027] The average number of remaining hydroxyl groups per glucose unit of cellulose acetate (residual hydroxyl degree) can be set in the range of 0 to 2.9. Hydroxy groups may remain from the viewpoint of the maximum strength, heat resistance, etc. of the cellulose acetate resin composition, and for example, the residual hydroxyl degree may be 0.01 or more, and even 0.1 or more. In particular, from the viewpoint of the fluidity of the cellulose acetate resin composition, the residual hydroxyl degree of the final product cellulose acetate is preferably 1.0 or less, more preferably 0.8 or less, and even more preferably 0.6 or less.
[0028] The molecular weight of cellulose acetate is preferably in the range of 10,000 to 400,000, more preferably in the range of 50,000 to 350,000, even more preferably in the range of 100,000 to 300,000, and even more preferably in the range of 150,000 to 250,000. If the molecular weight is too large, the fluidity of the cellulose acetate resin composition is reduced, making processing difficult, and uniform mixing may be difficult. Conversely, if the molecular weight is too small, physical properties such as impact resistance of the cellulose acetate resin composition may be reduced. This weight average molecular weight can be determined by gel permeation chromatography (GPC) (commercially available standard polystyrene can be used as a standard sample).
[0029] <Ingredient (B)> The cellulose-based resin composition of the present embodiment contains, as component (B), triphenyl phosphate (also referred to as "TPP"), triethyl phosphate, tributyl phosphate, tricresyl phosphate, cresyl di-2,6-xylenyl phosphate, and a cellulose derivative represented by the following formula (I):
[0030] [ka] The component (B) contains one or more phosphoric acid esters selected from the group consisting of compounds represented by the following formula: Component (B) functions as a flame retardant and a plasticizer, and can impart flame retardancy and processing stability to the resin composition. In addition, by using these specific phosphoric acid esters, a resin composition having high impact strength can be formed. Component (B) may be used alone or in combination of two or more.
[0031] In the compound represented by the above formula (I), n in formula (I) is an integer of 1 or more, preferably 1 or more and 3 or less, and particularly preferably n=1.
[0032] In one aspect of the present embodiment, it is preferable to use one or more phosphate esters selected from the group consisting of triphenyl phosphate, triethyl phosphate, tributyl phosphate, and tricresyl phosphate, from the viewpoint of high compatibility with cellulose acetate.
[0033] In one aspect of this embodiment, component (B) preferably contains triphenyl phosphate (TPP). In one aspect, the content of TPP in the total amount of component (B) is preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass%. TPP is difficult to volatilize and has high compatibility with component (A). In addition, the use of TPP allows the formation of a resin composition with high mechanical strength.
[0034] Examples of commercially available products that can be used as component (B) include Adeka STAB PFR (product name) manufactured by ADEKA CORPORATION, and TPP (product name) and PX-110 (product name) manufactured by Daihachi Chemical Industry Co., Ltd.
[0035] In one aspect of this embodiment, from the viewpoint of obtaining a molded article having high mechanical strength, it is preferable that the content of the phosphate ester (referred to as "phosphate ester (b')") having low compatibility with component (A) is small. Examples of the phosphate ester (b') include those represented by the following formula:
[0036] [ka] A compound represented by the following formula:
[0037] [ka] and a condensed phosphate ester-based flame retardant represented by [(CH3)2C6H3O]2P(O)OC6H4OP(O)[OC6H3(CH3)2]2. The content of the phosphate ester (b') in the resin composition is preferably 3 mass% or less, more preferably 1 mass% or less, and even more preferably 0 mass%.
[0038] In the cellulose-based resin composition, the content of component (A) is preferably more than 70 mass%, more preferably 72.5 mass% or more, and even more preferably 74 mass% or more, relative to the total content of components (A) and (B) being 100 mass%, and is preferably 80 mass% or less, more preferably 77.5 mass% or less.
[0039] In one aspect of the present embodiment, the content of component (B) is preferably 20% by mass or more, more preferably 22.5% by mass or more, and also preferably less than 30% by mass, more preferably 27.5% by mass or less, and even more preferably 26% by mass or less, relative to the total content of components (A) and (B) being 100% by mass. By having the content of component (B) within this range, a resin composition having excellent processing stability and flame retardancy can be obtained. In one aspect of the present embodiment, from the viewpoint of suppressing bleeding out, the content of component (B) is preferably 26% by mass or less, more preferably 25% by mass or less, and even more preferably 22.5% by mass or less, relative to the total content of components (A) and (B) being 100% by mass. If the content of component (B) is too high, bleeding may occur in a high-temperature and high-humidity environment. On the other hand, if the content of component (B) is too low, processing stability and flame retardancy may become insufficient.
[0040] The total content of components (A) and (B) relative to 100% by mass of the total amount of the cellulose-based resin composition is not limited, but is preferably 60% by mass or more, more preferably 70% by mass or more, and is preferably less than 90% by mass, more preferably 89.8% by mass or less, and even more preferably 89.5% by mass or less.
[0041] <Ingredient (C)> The cellulose-based resin composition of the present embodiment contains an anti-drip agent as component (C). By containing component (C), the cellulose-based resin composition shrinks when heated, and the molten resin can be prevented from dripping (drip) and spreading the combustion. As the anti-drip agent, a fluorine-based anti-drip agent (fluorine-containing polymer) is preferable, and it is more preferable to contain a fluorine-containing polymer that forms a fiber structure (fibril structure) in the resin composition. By blending a fluorine-containing polymer, the effect of suppressing the drip phenomenon during combustion can be improved.
[0042] Examples of the drip prevention agent include fluororesins such as polytetrafluoroethylene (PTFE), tetrafluoroethylene copolymers (e.g., tetrafluoroethylene / hexafluoropropylene copolymers, etc.), resins in which polytetrafluoroethylene is acrylic-modified, polyvinylidene fluoride, and polyhexafluoropropylene, and perfluoroalkanesulfonic acid alkali metal salt compounds or perfluoroalkanesulfonic acid alkaline earth metal salts such as sodium perfluoromethanesulfonate, potassium perfluoro-n-butanesulfonate, potassium perfluoro-t-butanesulfonate, sodium perfluorooctane sulfonate, and calcium perfluoro-2-ethylhexanesulfonate. In addition, various forms of fluoropolymers such as fine powder fluoropolymers, aqueous dispersions of fluoropolymers, mixtures of powder fluoropolymers and acrylonitrile-styrene copolymers, and mixtures of powder fluoropolymers and polymethyl methacrylate can also be used as the fluoropolymer. Similarly, silicone compounds such as silicone rubbers and layered silicates such as talc may be blended as other drip prevention agents. These may be used alone or in combination of two or more.
[0043] Among these, a fluorine-based drip prevention agent having fibril forming ability is preferred, and polytetrafluoroethylene (PTFE) is particularly preferred. The molecular weight of the fluorine-based drip prevention agent (particularly PTFE) is preferably 1 to 10 million, more preferably 2 to 9 million, in terms of number average molecular weight calculated from standard specific gravity. Such PTFE may be in the form of a solid or an aqueous dispersion. In one embodiment, the content of PTFE in the total amount of component (C) is preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass%.
[0044] In the cellulose-based resin composition, the content of component (C) is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.3% by mass or more, and even more preferably 0.5% by mass or more, and is preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1.0% by mass or less, based on the total content of component (A), component (B), component (C) and component (D) of 100% by mass. If the content of component (C) is too high, the processing stability may be reduced. On the other hand, if the content of component (C) is too low, the flame retardancy may be insufficient.
[0045] <Ingredient (D)> The cellulose-based resin composition of the present embodiment contains a metal hydroxide as component (D). By containing a metal hydroxide, the resin composition can have improved flame retardancy.
[0046] Examples of metal hydroxides include aluminum hydroxide, magnesium hydroxide, calcium hydroxide, etc. Among these, aluminum hydroxide is particularly preferred because it has a high heat absorbing effect and excellent flame retardancy. The surface of the metal hydroxide may be surface-treated with various organic substances such as epoxy resins and phenolic resins. The metal hydroxide may be used alone or in combination of two or more. In one embodiment, the content of aluminum hydroxide in the total amount of component (D) is preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass%.
[0047] The 50% particle size of metal hydroxide (median size, D 50 ) is not particularly limited, but is preferably 0.5 μm or more and 20 μm or less, more preferably 1 μm or more and 10 μm or less, and even more preferably 2 μm or more and 4 μm or less. When the 50% particle size of the metal hydroxide is within this range, it is excellent in dispersibility in the resin composition, leading to improved flame retardancy and mechanical properties. If the 50% particle size of the metal hydroxide is too small, the viscosity of the resin composition may increase and the moldability may decrease. In addition, the increase in viscosity may increase the shear force during kneading and molding, which may cause deterioration of other components. On the other hand, if the 50% particle size of the metal hydroxide is too large, unevenness may occur on the surface of the resin composition, resulting in a decrease in design. The average particle size of the metal hydroxide can be determined, for example, by measuring the volume-based median size by a diffraction / scattering method.
[0048] The content of component (D) (metal hydroxide) in the resin composition is preferably 10% by mass or more, more preferably 12.5% by mass or more, and even more preferably 15% by mass or more, relative to 100% by mass of the total content of components (A), (B), (C) and (D) (also referred to as "components (A) to (D)"). It is also preferably 20% by mass or less, and more preferably 17.5% by mass or less. If the content of component (D) is too low, the flame retardancy may be insufficient. On the other hand, if the content of component (D) is too high, the toughness may decrease, resulting in a resin composition with poor mechanical properties.
[0049] In one aspect of this embodiment, from the viewpoint of having both excellent flame retardancy and mechanical strength and being able to suppress exudation of component (B), it is preferable that in the cellulose-based resin composition, the content of component (B) is 20% by mass or more and less than 30% by mass, relative to 100% by mass of the total content of components (A) and (B), and the content of component (D) is 10% by mass or more and 20% by mass or less, relative to 100% by mass of the total content of components (A) to (D).
[0050] In one aspect of the present embodiment, from the viewpoint of obtaining a resin composition having particularly excellent flame retardancy, it is preferred that the content of component (B) is 22.5 to 26 mass% relative to 100 mass% of the total content of components (A) and (B), and that the content of component (D) is 12.5 to 17.5 mass% relative to 100 mass% of the total content of components (A) to (D).
[0051] As an example of this embodiment, for example, when the content of component (B) is 25 mass% relative to the total content of components (A) and (B) being 100 mass%, and the content of component (D) is 17.5 mass% relative to the total content of components (A) to (D) being 100 mass%, a resin composition with particularly excellent flame retardancy can be obtained (see Example 9 described later).
[0052] In one aspect of the present embodiment, from the viewpoint of obtaining a resin composition having particularly excellent toughness, the content of component (B) is preferably from 20% by mass to less than 30% by mass, and more preferably from 22.5% by mass to less than 30% by mass, relative to 100% by mass of the combined content of components (A) and (B), and the content of component (D) is preferably from 10% by mass to 17.5% by mass, and more preferably from 10% by mass to 12.5% by mass, relative to 100% by mass of the combined content of components (A) to (D).
[0053] From the viewpoint of obtaining a resin composition having excellent toughness, in a preferred aspect of this embodiment, the content of component (B) is 22.5% by mass or more and less than 30% by mass, relative to 100% by mass of the total content of components (A) and (B), and the content of component (D) is 10% by mass or more and 17.5% by mass or less, relative to 100% by mass of the total content of components (A) to (D).
[0054] Furthermore, from the viewpoint of obtaining a resin composition having excellent toughness, in one aspect of the present embodiment, it is preferred that the content of component (B) is 20% by mass or more and less than 30% by mass, relative to 100% by mass of the combined content of components (A) and (B), and that the content of component (D) is 10% by mass or more and 12.5% by mass or less, relative to 100% by mass of the combined content of components (A) to (D).
[0055] In one aspect of this embodiment, from the viewpoint of obtaining a resin composition having particularly excellent toughness, it is preferred that the content of component (B) is 22.5 mass% or more and less than 30 mass% relative to 100 mass% of the total content of components (A) and (B), and that the content of component (D) is 10 to 12.5 mass% relative to 100 mass% of the total content of components (A) to (D).
[0056] The cellulose-based resin composition according to the present embodiment may contain other components within a range that does not impair the desired properties when molded into a product. In one embodiment, for example, the total amount of components (A), (B), (C) and (D) is preferably set to a range of 75 to 100 mass% based on the entire cellulose-based resin composition, more preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and even more preferably 98 mass% or more.
[0057] The resin composition may contain, as other components, additives generally used in ordinary molding resin materials, within the scope of the present embodiment. Examples of such additives include colorants, antioxidants such as phenolic and phosphorus-based, light stabilizers, ultraviolet absorbers, antistatic agents, antibacterial and antifungal agents, and fillers. In particular, the resin composition may contain additives generally used in ordinary cellulose resins.
[0058] (Coloring agent) In one embodiment, the cellulose-based resin composition may include a colorant, such as a black colorant, for example, carbon black.
[0059] The content of the colorant such as a black colorant is not limited, but can be set in the range of 0.01 to 10 phr (0.01 to 10 parts by mass per 100 parts by mass of the total mass of the components other than the colorant in the cellulose-based resin composition, the standard of the content of the colorant is the same below) relative to the total mass of the components other than the colorant. In one embodiment, from the viewpoint of obtaining a sufficient coloring effect, the content of the colorant is preferably 0.05 phr or more, and preferably 0.1 phr or more, relative to the total mass of the components other than the colorant. From the viewpoint of suppressing the excess amount of the colorant while obtaining a sufficient coloring effect, it is preferably 5 phr or less, more preferably 3 phr or less, and even more preferably 2 phr or less.
[0060] From the viewpoint of appearance such as gloss, the content of the colorant is preferably 1 phr or less, more preferably 0.3 phr or less, even more preferably 0.2 phr or less, and even more preferably 0.1 phr or less.
[0061] If necessary, an inorganic or organic granular or fibrous filler can be added to the resin composition of the present embodiment. By adding a filler, the strength and rigidity can be further improved. Examples of fillers include mineral particles (talc, mica, calcined silica earth, kaolin, sericite, bentonite, smectite, clay, silica, quartz powder, glass beads, glass powder, glass flakes, milled fiber, wollastonite (or wollastonite), etc.), boron-containing compounds (boron nitride, boron carbide, titanium boride, etc.), metal carbonates (magnesium carbonate, heavy calcium carbonate, light calcium carbonate, etc.), metal silicates (calcium silicate, aluminum silicate, magnesium silicate, magnesium aluminosilicate, etc.), metal oxides (magnesium oxide, etc.), metal sulfates (calcium sulfate, barium sulfate, etc.), metal carbides (silicon carbide, aluminum carbide, titanium carbide, etc.), metal nitrides (aluminum nitride, silicon nitride, titanium nitride, etc.), white carbon, and various metal foils. Examples of fibrous fillers include organic fibers (natural fibers, paper, etc.), inorganic fibers (glass fibers, asbestos fibers, carbon fibers, silica fibers, silica-alumina fibers, wollastonite, zirconia fibers, potassium titanate fibers, etc.), metal fibers, etc. These fillers can be used alone or in combination of two or more.
[0062] In one aspect of this embodiment, the resin composition may contain glass fibers. The strength of the molded body is improved by the resin composition containing glass fibers. The glass fibers are not particularly limited, but the fiber length of the glass fibers before melt-kneading is preferably 0.5 mm or more, and preferably 30 mm or less, more preferably 10 mm or less. The cross-sectional shape of the glass fibers is not particularly limited, and examples thereof include circular, elliptical, oval, and non-circular. The fiber diameter of the glass fibers may be, for example, 3 to 20 μm when the cross-sectional area is converted into a perfect circle. In one aspect of this embodiment, the content of the glass fibers relative to the total mass of the resin composition may be 0 mass%, but is, for example, preferably 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 3 mass% or more, and is also preferably 20 mass% or less, more preferably 10 mass% or less, and even more preferably 8 mass% or less.
[0063] In one aspect, the resin composition of the present embodiment preferably contains a small amount of polylactic acid resin and aromatic polycarbonate resin. If the resin composition contains polylactic acid resin or aromatic polycarbonate resin, the compatibility with cellulose acetate is low, so that the composition becomes cloudy, and it is difficult to obtain sufficient flame retardancy and mechanical properties. The content of these components is preferably 3% by mass or less, more preferably 1% by mass or less, and even more preferably 0% by mass, based on the total mass of the resin composition.
[0064] <Method of producing cellulose-based resin composition> The method for producing the cellulose-based resin composition is not particularly limited, and for example, the cellulose-based resin composition can be obtained by melt-mixing the components (A), (B), (C) and (D) with other components as necessary using a normal mixer. As the mixer, for example, a compounding device such as a tumbler mixer, a ribbon blender, a single-screw or multi-screw mixer extruder, a kneading kneader, or a kneading roll can be used. After melt mixing, the mixture can be granulated into an appropriate shape as necessary, for example, pelletized using a pelletizer.
[0065] <Molded body> The molded article formed using the cellulose resin composition according to the present embodiment can be formed into a desired shape by a normal molding method, and the shape and thickness of the molded article are not limited. From the viewpoint of the strength of the molded article, the thickness is preferably 0.5 mm or more, more preferably 0.8 mm or more. Furthermore, from the viewpoint of flame retardancy, the thickness is preferably 1.0 mm or more, more preferably 1.6 mm or more, more preferably 2.0 mm or more, and even more preferably 3.2 mm or more. On the other hand, the upper limit of the thickness of the molded article is not particularly limited, and can be appropriately set according to the required shape, strength, etc., but sufficient physical properties can be obtained even if the thickness is set to, for example, 10 mm or less, or even 5 mm or less.
[0066] The cellulose-based resin composition according to the present embodiment can be molded into a molded article according to the intended use by a common molding method such as injection molding, injection compression molding, extrusion molding, or hot press molding.
[0067] The molded article formed using the cellulose-based resin composition according to the present embodiment has excellent flame retardancy and mechanical properties, and can be applied to housings, exteriors, decorative panels, and decorative sheets, and can be used in place of components used in, for example, electronic devices, home appliances, building materials, furniture, and automobiles. For example, it can be used in housings and exterior parts of electronic devices and home appliances, interior components of building materials, and interior materials of automobiles.
[0068] According to this embodiment, it is possible to provide products such as electronic devices, home appliances, automobiles, building materials, and furniture, which include a molded article formed using the resin composition according to the present invention.
[0069] Applications for electronic devices and home appliances include housings for computers, landlines, mobile phones, smartphones, tablets, POS terminals, routers, projectors, speakers, lighting equipment, copiers, multi-function printers, calculators, remote controls, refrigerators, washing machines, humidifiers, dehumidifiers, video recorders / players, vacuum cleaners, air conditioners, rice cookers, electric shavers, electric toothbrushes, dishwashers, broadcasting equipment, clock faces and exteriors, and cases for mobile devices such as smartphones.
[0070] Automotive applications include interior instrument panels, dashboards, cup holders, door trim, arm rests, door handles, door locks, steering wheels, brake levers, ventilators, shift levers, and the like. EXAMPLES
[0071] The present invention will be described in more detail below with reference to specific examples, but the present invention is not limited to these.
[0072] The components used in producing the resin compositions of the Examples and Comparative Examples are shown below.
[0073] <Component (A)> (a1) Cellulose acetate (CA) (manufactured by Daicel Corporation, product name: L-50, acetyl group introduction ratio (substitution degree) DS = 2.4, acetylation degree: 55%, polymerization degree based on 6% viscosity: 180) <Ingredient (B)> (b1) Triphenyl phosphate (TPP) (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TPP)
[0074] <Phosphate ester (b')> (b1') the following formula:
[0075] [ka] A compound represented by the formula (manufactured by ADEKA Corporation, product name: ADK STAB FP-600) (b2') the following formula:
[0076] [ka] A compound represented by the formula (manufactured by ADEKA Corporation, product name: Adeka STAB FP-900L)
[0077] (b3') [(CH3)2C6H3O]2P(O)OC6H4OP(O)[OC6H3(CH3)2]2 (manufactured by Daihachi Chemical Industry Co., Ltd., product name: PX-200)
[0078] <Ingredient (C)> (c1) Polytetrafluoroethylene (PTFE) (manufactured by Daikin Industries, Ltd., product name: Polyflon MPA FA-500H)
[0079] <Ingredient (D)> (d1) Aluminum hydroxide (manufactured by Nippon Light Metal Co., Ltd., product name: BE023) (average particle size: 2 μm) (d2) Aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd., product name: BE043-STE) (average particle size: 4 μm, surface treated with epoxy silane coupling agent)
[0080] <compatibility> In order to confirm the compatibility of component (a1) with each phosphate ester, they were mixed in a mass ratio of component (a1):phosphate ester = 80:20, kneaded in the same manner as the kneading method described below, and the appearance was observed.
[0081] When component (b1) was used as the phosphate ester, it was confirmed that the solution was transparent and had high compatibility without any cloudiness.
[0082] When components (b1'), (b2') and (b3') were used as the phosphate ester, the thermoplasticity was insufficient, and the mixture could not be discharged from the kneader and could not be kneaded.
[0083] <Examples 1 to 10 and Comparative Examples 1 to 5> The materials shown in Tables 2 to 4 were prepared as the constituent materials of the target cellulose-based resin composition. Next, the constituent materials were thoroughly mixed by hand mixing in the blending ratios shown in Tables 2 to 4. The resin materials were dried in advance at 80°C for 5 hours. In Tables 2 to 4, the units of numerical values relating to the blending ratios are mass%. The contents of components (a1) and (b1) are the ratios (mass%) to the total of 100 mass% of components (a1) and (b1). The contents of components (c1), (d1), and (d2) are the ratios (mass%) of each component to the total of 100 mass% of components (a1), (b1), (c1), (d1), and (d2).
[0084] (Mixing method) The mixture was fed into a co-rotating twin screw extruder (STEER, product name: Omega30H [φ30, L / D=60]), kneaded at 200°C and 120 rpm, cooled with water, recovered, and pelletized. The pellets were dried at 80°C for 5 hours.
[0085] (Preparation of specimen for measuring Charpy impact value: Evaluation specimen 1) The obtained pellets were dried again at 80° C. for 5 hours immediately before molding, and used to produce a molded body (evaluation sample 1) having the following shape using an injection molding machine (manufactured by Toshiba Machine, product name: EC20P).
[0086] Molded body: JIS K 7162 test piece 1A shape At that time, the molding conditions were set as follows: Molding machine cylinder temperature: 190-230℃ Mold temperature: 60-70℃ Holding pressure: 60-100MPa
[0087] (Preparation of combustion test specimen: Evaluation specimen 2) The obtained pellets were dried again at 80° C. for 5 hours immediately before molding, and used to produce a molded body (evaluation sample 2) having the following shape using an injection molding machine (manufactured by Toshiba Machine, product name: EC20P).
[0088] Molded body: Length 125mm, width 13mm, thickness 1.6mm, 2.0mm, 3.2mm At that time, the molding conditions were set as follows: Molding machine cylinder temperature: 190-230℃ Mold temperature: 60-70℃ Holding pressure: 60-100MPa
[0089] <Flammability test (UL94V test)> Flammability tests were conducted in accordance with the UL94 test (flammability test for plastic materials for equipment parts) established by Underwriters Laboratories after leaving the test specimens (evaluation sample 2) obtained by injection molding for 48 hours in a temperature-controlled room at a temperature of 23°C and humidity of 50%. UL94V is a method for evaluating flame retardancy based on the burning time and dripping property after applying a burner flame (20±1mm flame) to the bottom end of a test specimen of a specified size held vertically for 10 seconds, and is classified into the classes shown in Table 1 below.
[0090] [Table 1]
[0091] The flame retardancy ranking from best to worst is V-0, V-1, V-2. However, materials that do not fall into any of the V-0 to V-2 rankings (low flame retardancy) are classified as V- non-compliant.
[0092] The flaming burning time is the length of time that the test specimen continues to burn with a flame after the ignition source (burner) is removed, where t1 is the burning time after the first flame contact, t2 is the burning time after the second flame contact, and t3 is the afterglow (flameless burning) time after the second flame contact. The second flame contact is performed by immediately contacting the test specimen with the burner flame for 10 seconds if the flame goes out after the first flame contact. The ignition of cotton by dripping is determined by whether the cotton used for marking, located 300±10 mm below the bottom end of the test specimen, is ignited by dripping from the test specimen.
[0093] <Charpy impact test> A Charpy impact test was carried out using evaluation sample 1 in accordance with JIS K7111-1 (with notch: Type A (notch cutter tip R0.25 mm)).
[0094] <Exudation test> The evaluation sample 1 was placed in a thermo-hygrostat at 60° C. and 85% RH, and the presence or absence of exudation after 24 hours was visually evaluated. When no exudation was observed, it was marked with ◯, and when exudation was observed, it was marked with ×.
[0095] The results are shown in Tables 2 to 4.
[0096] [Table 2]
[0097] [Table 3]
[0098] [Table 4]
[0099] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.
[0100] A part or all of the above embodiments may be described as follows, but the disclosure of the present application is not limited to the following supplementary notes.
[0101] (Appendix 1) Component (A): Cellulose acetate, Component (B): triphenyl phosphate, triethyl phosphate, tributyl phosphate, tricresyl phosphate, cresyl di-2,6-xylenyl phosphate, and a compound represented by the following formula (I):
[0102] [ka] and one or more phosphate esters selected from the group consisting of compounds represented by Component (C): Anti-drip agent, Component (D): a metal hydroxide, Including, The content of component (B) is 20% by mass or more and less than 30% by mass relative to 100% by mass of the total content of components (A) and (B), A cellulose-based resin composition, in which the content of component (D) is 10% by mass or more and 20% by mass or less relative to 100% by mass of the total content of components (A) to (D).
[0103] (Appendix 2) 2. The cellulose-based resin composition according to claim 1, wherein the component (B) comprises triphenyl phosphate.
[0104] (Appendix 3) 3. The cellulose-based resin composition according to claim 1, wherein the component (D) comprises aluminum hydroxide.
[0105] (Appendix 4) 4. The cellulose resin composition according to any one of claims 1 to 3, wherein the component (C) comprises a fluorine-based anti-drip agent.
[0106] (Appendix 5) 5. The cellulose resin composition according to any one of claims 1 to 4, wherein the component (C) comprises polytetrafluoroethylene.
[0107] (Appendix 6) The cellulose-based resin composition according to any one of Appendices 1 to 5, wherein the content of component (C) is 0.01% by mass or more, and preferably 0.2% by mass or more and 2% by mass or less, relative to 100% by mass of the total content of components (A) to (D).
[0108] (Appendix 7) The cellulose-based resin composition according to any one of claims 1 to 6, wherein the content of component (D) is 12.5% by mass or more and 17.5% by mass or less, relative to 100% by mass of the total content of components (A) to (D).
[0109] (Appendix 8) The cellulose-based resin composition according to any one of claims 1 to 7, wherein the content of component (B) is 22.5% by mass or more and 26% by mass or less, relative to 100% by mass of the total content of components (A) and (B).
[0110] (Appendix 9) A molded article formed using the cellulose resin composition according to any one of claims 1 to 8.
[0111] This application claims priority based on Japanese Patent Application No. 2021-124850, filed on July 29, 2021, the disclosure of which is incorporated herein in its entirety.
[0112] Although the present invention has been described above with reference to the embodiments and examples, the present invention is not limited to the above-mentioned embodiments and examples. Various modifications that can be understood by those skilled in the art can be made to the configuration and details of the present invention within the scope of the present invention.
Claims
1. Component (A): Cellulose acetate, Component (B): triphenyl phosphate, triethyl phosphate, tributyl phosphate, tricresyl phosphate, cresyl di-2,6-xylenyl phosphate, and a compound represented by the following formula (I): 【Chemistry 1】 and one or more phosphate esters selected from the group consisting of compounds represented by Component (C): an anti-drip agent; Component (D): a metal hydroxide, Including, The content of component (B) is 22.5% by mass or more and 26% by mass or less relative to 100% by mass of the total content of components (A) and (B), With respect to 100% by mass of the total content of components (A) to (D), The content of component (C) is 0.01% by mass or more and 2% by mass or less, A cellulose-based resin composition having a component (D) content of 12.5 mass% or more and 17.5 mass% or less.
2. The cellulose-based resin composition according to claim 1 , wherein the component (B) comprises triphenyl phosphate.
3. The cellulose-based resin composition according to claim 1 or 2, wherein the component (D) comprises aluminum hydroxide.
4. The cellulose-based resin composition according to claim 1 or 2, wherein the component (C) comprises a fluorine-based anti-drip agent.
5. The cellulose-based resin composition according to claim 1 or 2, wherein the component (C) comprises polytetrafluoroethylene.
6. A cellulose-based resin composition described in claim 1 or 2, wherein the total amount of components (A), (B), (C) and (D) is 95 mass% or more relative to the total amount of the cellulose-based resin composition.
7. A cellulose-based resin composition as described in claim 1 or 2, which does not contain a hydrolysis inhibitor.
8. A cellulose-based resin composition as described in claim 6, which does not contain a hydrolysis inhibitor.
9. A molded article formed using the cellulose resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Resin composition, molded product, electrical product, and method for producing the resin composition
JP2005162871A
Resin composition and molding comprising the same
JP2006111858A
Flame retardant thermoplastic resin composition
JP2011168798A
Resin composition, resin composition for injection molding, and housing for electric / electronic device
JP2011241236A
Resin composition, and resin molded article
JP2012092156A